2019
DOI: 10.3390/rs11192314
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of IMERG-V06 Precipitation Product over Different Hydro-Climatic Regimes in the Tianshan Mountains, North-Western China

Abstract: This study presents an assessment of the version-6 (V06) of the Integrated Multi-satellitE Retrievals for Global Precipitation Measurement (IMERG) product from June 2014 to December 2017 over different hydro-climatic regimes in the Tianshan Mountains. The performance of IMERG-V06 was compared with IMERG-V05 and the Tropical Rainfall Measuring Mission (TRMM) 3B42V7 precipitation products. The precipitation products were assessed against gauge-based daily and monthly precipitation observations over the entire sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 60 publications
(62 reference statements)
4
37
0
Order By: Relevance
“…However, V05, with a real enhancement, estimates precipitation with more accuracy in comparison with V03 and V04. Sharifi et al (2019) and Anjum et al (2019) could not find any improvement in V06 compared to the V05 across Austria and northwestern China, respectively. However, it is reported that the retrieval algorithm of IMERG V06 has benefited from several major improvements compared to V05, that is, a new morphing approach, advancements in the calibration, and refinement in the CMORPH-Kalman filter (Anjum et al 2019).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…However, V05, with a real enhancement, estimates precipitation with more accuracy in comparison with V03 and V04. Sharifi et al (2019) and Anjum et al (2019) could not find any improvement in V06 compared to the V05 across Austria and northwestern China, respectively. However, it is reported that the retrieval algorithm of IMERG V06 has benefited from several major improvements compared to V05, that is, a new morphing approach, advancements in the calibration, and refinement in the CMORPH-Kalman filter (Anjum et al 2019).…”
Section: Discussionmentioning
confidence: 87%
“…Sharifi et al (2019) and Anjum et al (2019) could not find any improvement in V06 compared to the V05 across Austria and northwestern China, respectively. However, it is reported that the retrieval algorithm of IMERG V06 has benefited from several major improvements compared to V05, that is, a new morphing approach, advancements in the calibration, and refinement in the CMORPH-Kalman filter (Anjum et al 2019). It should be noted that, in the new morphing scheme, the MERRA-2 variables are used instead of infrared data (Huffman et al 2015).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…As the spatiotemporal resolution and coverage of GPM have been extended beyond the TRMM resolution and coverage, the performance of the GPM IMERG products needs to be evaluated and validated globally.Several studies have compared the GPM IMERG and TRMM products with ground-based measurements, i.e., rain gauge and weather radar [4,6,10,[15][16][17][18][19], considering their hydrological applications [14,[20][21][22]. Also, different GPM IMERG products regarding temporal resolutions have been evaluated considering various climatic and topographic conditions using various statistical measures across the world [5,[23][24][25][26][27][28][29][30]. Although most of these studies confirmed the improvement of the IMERG products relative to those of the TRMM Multi-satellite Precipitation Analysis (TMPA), a more comprehensive investigation is still essential to better understand the IMERG performance in various regions of the world taking into consideration different products' versions and temporal resolution.…”
mentioning
confidence: 99%